Corpus Linguistics Research: Prefix Analysis on Technological Article from abcnews.go.com - Rizky Dwi Cahyo (Faculty of Education and Teachers Training, 2021)
AbstractAn affix is a morpheme attached to a word's root to make a new or word form. There are two kinds of affixes, the first is a bound morpheme that comes after the root of a word and is called suffix, and the second is, bound morpheme that comes before the base of the word is called prefix. Prefix process in English relating to negative and positive prefixes. The example of the negative prefix is in, un, dis, mis, and ill. While positive ones such as out, re, super, multi, under, and over. This paper aims to get information about prefixes in the technological article. abcnews.go.com is one of many big websites that contain the newest articles and news around the world. This study concludes that the readers expected to know about prefixes.